Chemical constituents from the fruits of Solanum nigrum and their chemotaxonomic significance. (August 2022) - Yang, Bo-Han; Zhang, Yi-Jie; Bai, Ming; Zhang, Qian; Li, Chen-Xi; Huang, Xiao-Xiao; Song, Shao-Jiang
Abstract: A phytochemical investigation of the fruits of Solanum nigrum L. led to the isolation of 17 compounds including ten lignans (1 –10 ) and seven amide alkaloids (11 –17 ). Their structures were elucidated by extensive spectroscopic methods and comparison with literature data. All the compounds were isolated from S.nigrum, firstly. Besides, a plant network analysis of all isolated compounds was presented to demonstrate the chemotaxonomic significance. The research clarifies the chemotaxonomic significance, and it accordingly contributes to further knowledge of the chemical diversity of S. nigrum . Highlights: All isolated compounds were from the fruits of Solanum nigrum L. Compounds 4–10, 15 were gotten from genus Solanum and compounds 2, 4–10 and 15 were gained from family Solanaceae initially. The chemotaxonomy of the isolated compounds was discussed.